DATA LINKAGE FOR EVALUATING MATERNAL INFLUENCES ON INFANT MORTALITY AND MALTREATMENT IN CANADA. (18th May 2018) - Smith, Jennifer; Guttmann, Astrid; Kopp, Alexander; Shouldice, Michelle; Harron, Katie
Abstract: BACKGROUND: A number of social risk factors are reported to increase infant mortality rates and child maltreatment. Public health programs attempt to mitigate risk factors and improve outcomes for infants. This study aimed to explore the association of exposure factors in mothers with infant mortality and maltreatment in Ontario. OBJECTIVES: Objectives for this study included: 1. Describe prevalence of infant mortality and maltreatment in Ontario. 2. Explore how maternal risk factors influence infant mortality and maltreatment. DESIGN/METHODS: This was a population-based study of 845, 567 infants born between April 1, 2005 and March 31, 2015 using administrative and healthcare databases available at the Institute of Clinical Evaluative Sciences (ICES). Maternal risk factors were selected based on public health home visiting referral criteria. These exposures included, maternal adversity (substance abuse, intimate partner violence, homelessness), newcomer status (new to Canada in past 3 years) and young maternal age (less than 22 years of age). The primary outcome measure was all-cause mortality of infants less than 12 months age. The secondary outcome measures were combined fatal and non-fatal child maltreatment outcomes and were defined using International Classification of Diseases for maltreatment diagnoses. Baseline characteristics and outcomes were described. The association between maternal risk factors and infant mortality and maltreatment was analysed using multivariable logistic modelling, including analysis by type of maternal risk factors and number of risk factors. RESULTS: All-cause deaths were present in 0.14% and combined fatal and non-fatal maltreatment outcomes were present in 0.05% of the study population. Young maternal age increased the risk of all-cause mortality 2.4 times (n 171, OR 2.4, 95% CI 2.0–3.0) and maltreatment 6.3 times (n 292, OR 6.3, 95% CI 5.0–7.8). Mental health diagnosis increased the odds of maltreatment by 90% (n 209, OR 1.9, 95% CI 1.5–2.4). Adversity increased the odds of maltreatment by 63% (n 40, OR 1.63, 95% CI 1.0–2.6). The risk of maltreatment also increased as the number of risk factors increased with an OR of 3.5 (95% CI 2.9–4.4) with one risk factor, an OR of 8.2 (95% CI 5.9–11.4) with two risk factors, and an OR of 10.9 (95% CI 5.7 20.7) with three or more risk factors. Newcomer status was not associated with increased risk of maltreatment and mortality. Gestational age showed increasing ORs as prematurity increased. Material deprivation was included as a covariate and was associated with increased risk of maltreatment with increased level of deprivation. CONCLUSION: Young maternal age carried the greatest risk of death and maltreatment in infants. There was also an increasing risk of infant mortality and maltreatment with increasing number of risk factors. These findings are important for ensuring public health interventions are targeting the most vulnerable populations with the aim of preventing maltreatment.